Comparison of echocardiography and angiography in determining the cause of severe aortic regurgitation. Issue 1 (January 1984) - DePace, N L; Nestico, P F; Kotler, M N; Mintz, G S; Kimbiris, D; Goel, I P; Glazier-Laskey, E E; Ross, J
Abstract : To assess the accuracy of echocardiography in determining the cause of aortic regurgitation M mode and cross sectional echocardiography were compared with angiography in 43 patients with predominant aortic regurgitation. Each patient had all three investigations performed during the same admission to hospital. In each instance, the cause of aortic regurgitation was confirmed at surgery or necropsy. Seventeen patients had rheumatic aortic valve disease, 13 bacterial endocarditis with a perforated or partially destroyed cusp, five a bicuspid aortic valve (four with a history of endocarditis), and eight aortic regurgitation secondary to aortic root dilatation or aneurysm. Overall sensitivity of echocardiography and aortography was 84% in determining the cause of aortic regurgitation. Thus, rheumatic valve disease and endocarditis appear to be the most common causes of severe aortic regurgitation in this hospital based population. Furthermore, echocardiography is a sensitive non-invasive technique for determining the cause of aortic regurgitation and allows differentiation of valvular from root causes of aortic regurgitation.